Pendampingan masyarakat dalam pembuatan Ecobrick sebagai Alternatif Pengelolaan Sampah Plastik di Desa Tajungan Kamal Bangkalan - Agung Setyawan (BEKTI : Jurnal Pengabdian kepada Masyarakat, 2022)
Every activity carried out by humans will produce waste, both agricultural activities, industry, domestic activities, and other activities. Based on its nature, waste is divided into 2 types, namely, organic (easily decomposed) and inorganic (difficult to decompose). One example of inorganic waste is plastic, plastic is still widely used in the daily life of the Indonesian people, so it affects the amount of plastic waste produced every day. However, this has not been balanced with public awareness and understanding regarding the impacts produced by plastic waste and alternatives to proper plastic waste management. This has led to a higher amount of plastic waste, especially from the household sector. Therefore, there is a need for socialization and mentoring activity in managing plastic waste, one of the alternatives to plastic waste management that can be used is ecobricks. The implementation methods used in this activity are socialization of the impact of plastic waste and ecobricking methods, ecobricking practices and assistance, and evaluation. This activity is located in Tajungan Village, Kamal, Bangkalan. This socialization and mentoring activity aims to improve the knowledge and skills of the community in managing plastic waste independently so that the production of plastic waste especially from the household sector can be reduced.